Ciò che è confuso e tuttavia più manifesto: Osservazioni sul concetto di fenomeno a partire da Husserl - Deodati, Marco (B@belonline, 2020)
The essay aims to clarify some aspects related to the concept of phenomenon starting from Husserlian reflection, in which this notion presents a remarkable complexity. In the first instance, we intend to reconstruct the fundamental passages through which Husserl, after the first edition of the Logical Investigations, comes to conceive the phenomenon in the double sense of manifestation and self-showing thing. Secondly, we want to highlight that the constitutive co-belonging of these two dimensions allows us to read the so-called life-world in terms of the world of doxa, that is, those subjective-relative experiences in which every possible donation of sense is rooted.